The informative value of magnetic resonance imaging with the application of the protocol of diffusion-weighted images in the assessment of the endometrium when multiple neoplasias - V. N. Diomidova; M. A. Safonova; O. V. Zakharova; A. N. Dmitrieva; O. A. Efimova (Исследования и практика в медицине, 2020)
Purpose of the study. To study the diagnostic informativeness of magnetic resonance imaging (MRI) with the assessment of diffusion- weighted images and the measured diffusion coefficient in the diagnosis of endometrial tumor lesions in polyineoplasias.Materials and methods. The article presents the results of a study of patients with synchronous and metachronous polyneoplasias who were in the AU "Republican clinical oncological dispensary" of the Ministry of health of the Chuvash Republic from 2014 to 2018. All were performed magnetic resonance imaging on Excelart Vantage Atlas (Toshiba, Japan, 1.5 T), ultrasound (Aplio, Xario and Nemio, Toshiba, Japan; Sono Scape, China), x-ray computed tomography on Light Speed VEX Plus and Light Speed RT 16 (GE, USA). All MRI results were compared with morphological data obtained afterhistomorphological examination of the postoperative material. The differences were considered significant at values p≤0.05.Results. 80 cases of endometrial tumor lesions in polyineoplasias (N1a) were detected, which was 44.7% of all cases of the main group (N1; n=179), of which metachronous polyineoplasias were found in 56 (70.0%), synchronous — in 11 (13.7%), combined — in 13 (16.3%) patients. The informative value of MRI in the diagnosis of malignant neoplasms with lesions of the endometrium when multiple neoplasias were: sensitivity of 91.3%, specificity — 82,4%, accuracy was 89.7% (p<0.001).Conclusions. Magnetic resonance imaging using the diffusion- weighted image Protocol with an assessment of the measured diffusion coefficient has shown high information both in the diagnosis of primary endometrial tumor lesions in primary multiple malignancies, and in establishing the stage of the tumor process and in the diagnosis of subsequent malignancies.